UPAYA PENINGKATAN KUALITAS BAMBU DENGAN STABILISASI DIMENSI - Kusumaningsih, Karti Rahayu (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2012)
Bamboo is multipurpose plant widely used for many purposes. One of problem in the utilization of bamboo is dimensional change caused by difference of relative humidity. Hence, to overcome this problem is used dimensional stabilization to decrease shrinkage and increase the quality of bamboo. The purpose of this study is to know the effect of bamboo species and concentration of urea stabilizer against tangential and radial shrinkage, Anti Shrink Efficiency (ASE) and ratio of tangential and radial shrinkage (T/R ratio). The bamboo investigated are Gigantochloa apus and Dendrocalamus asper using bulking method at 20%, 40% and 60% urea concentration. Results of the study showed that interaction between bamboo species and urea consentration was very significant effect against tangential and radial shrinkage and Anti Shrink Efficiency (ASE). G. apus stabilized in 20% urea concentration and D. asper stabilized in 60% urea concentration gived lower shrinkage and high tangential and radial of Anti Shrink Efficiency with criteria of dimensional stability was very successful. G. apus had higher dimensional stability than D. asper. Keywords : Bamboo, Dimensional stabilization, Shrinkage, Anti Shrink Efficiency